Does God belong in public schools? - Greenawalt, Kent, 1936-2023 (Princeton University Press, 2005)
Controversial Supreme Court decisions have barred organized school prayer, but neither the Court nor public policy exclude religion from schools altogether. In this book, one of America's leading constitutional scholars asks what role religion ought to play in public schools. Kent Greenawalt explores many of the most divisive issues in educational debate, including teaching about the origins of life, sex education, and when--or whether--students can opt out of school activities for religious reasons. Using these and other case studies, Greenawalt considers how to balance the country's constitut.